THE CORRELATION BETWEEN LEVEL OF HEMOGLOBIN, HEMATOCRIT, AND THROMBOCYTES OF MOTHER AND ASPHYXIA IN NEWBORN - Norwidya Priansiska; Abkar Raden; Dewi Rokhanawati (Belitung Nursing Journal, 2018)
Background: Infant mortality in Indonesia is at the highest level among the countries in South East Asia. Asphyxia in newborn has become the second risk factor for infant mortality. Objective: The objective of this study was to investigate the correlation between the level of hemoglobin, hematocrit, and thrombocytes of the mothers and asphyxia in the newborns at Panembahan Senopati Bantul Hospital, Indonesia. Methods: The study employed case-control method with 282 samples, which 141 assigned in the case and control group. This study used medical record of the patients as the secondary data. Chi-square, multiple logistic regression, and Odds Ratio Calculation (OR) were used for data analysis. Results: There was a meaningful correlation between the level of hemoglobin (OR=2.3, 95%CI=1.3-4), hematocrit (OR=4.3, 95%CI=1.4-13.4, and thrombocytes (OR=5.3, 95%CI=1.14-24.6) of the mothers and asphyxia in newborns. Thrombocytes was the most dominant factor related to asphyxia in newborns. Conclusion: Mothers who have hemoglobin, hematocrit and thrombocytes levels under the normal have more than two times risk of asphyxia in their newborn than mothers who have normal hemoglobin, hematocrit and thrombocytes levels.